Exclusive Breastfeeding Practice and Associated Factors among Mothers Attending Private Pediatric and Child Clinics, Addis Ababa, Ethiopia: A Cross-Sectional Study - Laykewold Elyas; Amha Mekasha; Amha Admasie; Etagegnehu Assefa (Hindawi Limited, 2017)
Background. The prevalence of exclusive breastfeeding (EBF) is globally low (35%) in sub-Saharan Africa, whereas it is 58% in Ethiopia. Exclusive breastfeeding has the potential to prevent 11.6% of under-five deaths in developing countries. Therefore, the main objective of this study was to assess the exclusive breastfeeding practice and associated factors on mothers attending private pediatric and child clinics in Addis Ababa, Ethiopia. Methods. An institutional-based cross-sectional study design was used. A total of 380 samples were obtained. Data were collected using a self-administered questionnaire. Data was entered and analyzed using SPSS version 16. Descriptive statistics and logistic regression analysis were used. Results. From 380 mothers, only 44.2% of the mothers practiced EBF. Two hundred (52.6%) mothers started breastfeeding within 1 hour of delivery; 161 (42.4%) of the mothers gave extra food before six months, and 244 (64.2%) believed that exclusive breastfeeding was sufficient. Moreover, 288 (75.8%) mothers breastfed their children eight or more times per day. Spontaneous vaginal delivery was a significant factor to practice EBF (AOR: 1.86, 95% CI: 1.19-2.89). Conclusion. EBF practice in this study was low. Spontaneous vaginal delivery was a significant factor for EBF; hence, it is very crucial to promote EBF.